2017
DOI: 10.1097/opx.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Repeatability of a Novel Dynamic Visual Acuity System

Abstract: moV& provides good clinical measures of static visual acuity that are comparable to both Snellen and ETDRS measures. Dynamic visual acuity measures demonstrate good test-retest repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The fact that the test used in the current study is not the same as those reported in the current literature prevents a direct comparison of the results with those from other studies. However, the values found are in the same order of magnitude of those from other published papers …”
Section: Discussionsupporting
confidence: 81%
“…The fact that the test used in the current study is not the same as those reported in the current literature prevents a direct comparison of the results with those from other studies. However, the values found are in the same order of magnitude of those from other published papers …”
Section: Discussionsupporting
confidence: 81%
“…Dynamic VA was measured using the computer program moV& (V&mp Vision Suite, Waterloo, Canada) with a single moving tumbling E letter that moved in a random walk trajectory at a speed of 1 m/s and was presented on a high definition television screen (50 or 60 display, 60 Hz refresh rate and 1920 × 1080 resolution, illuminance at 130-150 lx) at a distance of 1 m (Hirano et al, 2017). The initial size of the letter presented was 0.60 log units bigger than the participant's static VA to make sure that the subject started the test from a suprathreshold level, and the maximum letter size presentable on this screen was 2.60 logMAR at a distance of 1 m. Five targets were presented per 0.1 logMAR step, and the display time was set to be unlimited to ensure adequate time to respond to the direction of the letter E. The test sequence continued until the participant could no longer correctly identify three out of five targets of the same size.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, values of 0.00 log CS and 0.0% were assigned for these participants’ CS and VF measures, respectively. Dynamic VA has been reported to be between 0.20 and 0.30 logMAR worse than the static VA in individuals with normal vision ( Hirano et al, 2017 ), but it was impossible to predict how much worse dynamic VA would be relative to static VA for each individual with vision impairment. Assigning 0.00 logMAR values for GLS, GLR, or LS for these participants would indicate that their static VA did not change with glare or increased light intensity rather than they were unable to do the task.…”
Section: Methodsmentioning
confidence: 99%
“…SVA was measured using an Early Treatment Diabetic Retinopathy Study chart at 1 m and/or the Berkeley Rudimentary Vision Test at 0.25 to 1.00 m (as per the test protocol). 1,26 Dynamic visual acuity was measured using the computer program moV& (V&mp Vision Suite, Waterloo, Canada), which used a single tumbling E letter that moved in a random walk trajectory at a speed of 1 m/s, and was presented on a high-definition television screen (50" or 60" display, 60 Hz refresh rate and 1920 × 1080 resolution, illuminance at 130-150 lux) at a distance of 1 m. 27 The initial size of the letter presented was 0.60 log units bigger than the participant's static visual acuity to make sure that the subject started the test from a suprathreshold level, and the maximum letter size presentable on this screen was 2.60 logMAR at a distance of 1 m. Five targets were presented per level of visual acuity measured and the target display time was set to be unlimited to ensure adequate time to respond to the direction of the letter E. The translational (up or down movement) and radial (in or out movement) MP tests were designed to quantify how well local moving elements in visual scenes are integrated to create a global moving stimulus. We measured both TMP and RMP using random dot kinematograms that consisted of 100 individual, full-contrast, local dots that were equivalent to the size of the target detail of a 2.0 logMAR letter (Dalton K, et al IOVS 2017;58 8:ARVO E-Abstract 4693).…”
Section: Methodsmentioning
confidence: 99%